Kepemimpinan Ketua Yayasan Shine Al-Falah Pada Pondok Pesantren Perkampungan Minangkabau Dalam Pendidikan Kaum Dhuafa Kota Padang - Ahmad Sabri; Heri Priyanto (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
In the view of Islam, the Dhuafa (orphans, destitute, neglected children) occupy the privileges of Allah SWT and His Apostles as in Surah Al-Maun Verses 1-3, for this, it is needed help from individuals and institutions to be able to maintain survival, and not displaced to become irresponsible people. This study illustrates how the Chairman of the Shine Al-Falah Foundation's leadership in fostering the Minangkabau village boarding school for the poor and the Shine Al-Falah Foundation's synergy with the government, donors, and the community. This research uses a qualitative method with a descriptive type. Primary data sources are the chairman, the supervisor of the Shine Al-Falah foundation, while the secondary data are the leader of the Islamic Boarding School, the laziswaf management, the orphanage management, the male / female boarding supervisor and the students. Data collection uses observation, interviews, and documentation. The results showed the leadership of the chairman of the Foundation Shine Al-Falah succeeded in fostering the Minangkabau village boarding school to be able to continue to exist in continuing education development by building participatory leadership to all stakeholders and trying to build synergy with relevant government agencies, the community and donors to run the program planned to meet the educational needs, infrastructure, basic food needs and so on that are suitable for children of poor people in Padang city, especially for children in the Minangkabau Village Islamic Boarding School.